AGILE SYSTEM‐SECURITY: SUSTAINABLE SYSTEMS EVOLVE WITH THEIR ENVIRONMENT. Issue 2 (July 2016) - Dove, Rick
ABSTRACT: This overview article and the accompanying essays lay groundwork for, and perspectives on, agile system‐security guidance for systems engineering. No expertise in security engineering is assumed or necessary to glean systems engineering value. With an agile attack environment, agile system‐security is necessary. Agile security is defined as both a resilient (reactive) and composable (proactive) capability to effectively address the unpredictable and ever‐evolving environment of adversarial attacker and attack methods – a systems‐engineered capability enabled by the system's architecture and design. This definition is agnostic to the type of system, and can encompass information systems, cyberphysical systems, physical systems, enterprise systems, social systems, and military systems. The systems engineering community is addressed with considerations felt necessary for next‐generation agile security, enabled by thoughtful systems engineering.